Design and Simulation of Rectangular Slot Antennas Using the Finite Element Method in Python - Hamza, Zahraa A. (International Journal of Electrical and Computer Engineering Systems, 2025)
The design and simulation of rectangular slot antennas using a Python-based Finite Element Method (FEM) framework are presented in this study, addressing the limitations of costly and resource-intensive commercial electromagnetic tools and the proposed open-source implementation leverages Python's computational ecosystem—integrating Gmsh for mesh generation, FEniCS for FEM discretization, and SciPy for sparse matrix solving—to provide an accessible and customizable platform for antenna analysis. Validation against Computer Simulation Technology (CST) and High Frequency Structure Simulator (HFSS) demonstrates exceptional agreement, with return loss (S11) deviations below 0.5 dB, radiation efficiencies exceeding 85%, and impedance matching within 2 Ω of the target 50 Ω, parametric studies reveal the impact of slot dimensions and substrate properties on resonant frequency and bandwidth, while computational benchmarks highlight Python-FEM's competitive performance, achieving solve times under 20 seconds for meshes with 180 MB memory usage and the framework's accuracy, coupled with its open-source flexibility, bridges the gap between academic research and industrial prototyping, particularly for applications in 5G, IoT, and radar systems, future enhancements, like Graphics Processing Unit (GPU) acceleration and multi-physical coupling, are proposed to further advance its scalability and versatility in next-generation antenna design.